Increased MCHC*RDW-SD interaction values: indicators of neurological impairment in lead-poisoned children - Ying, Qingji; Ye, Mengsi; Zhang, Tingting; Xia, Zhaobo; Chen, Huale (PeerJ, 2024)
Background The neurotoxic effects of lead in children can have long-lasting and profound impacts on the developing nervous system. This study aimed to identify a reliable and easily accessible biomarker to monitor neurological impairment in lead-poisoned children. Methods We analyzed hematological data from 356 lead-poisoned children, comparing them with age and gender-matched healthy controls. Multivariate logistic regression and receiver operating characteristic (ROC) analysis were employed to identify and evaluate potential biomarkers for neurological damage. Results Significant changes in erythrocyte parameters were observed in lead-poisoned children. Upon further analysis, increased mean corpuscular hemoglobin concentration (MCHC) and red cell distribution width-standard deviation (RDW-SD) interaction values were found to be significantly associated with neurological impairment. The MCHC*RDW-SD interaction model demonstrated an AUC of 0.76, indicating its effectiveness in reflecting neurological damage. Additionally, the MCHC*RDW-SD Interaction value showed weak or no correlation with other erythrocyte parameters, suggesting its independence as an indicator. Conclusion Our findings propose the increased MCHC*RDW-SD interaction value as a robust and independent biomarker for detecting neurological impairment in lead-poisoned children. This underscores the potential of utilizing specific erythrocyte parameters for screening the neurotoxic effects of lead exposure in pediatric populations.
Keywords: Mean corpuscular hemoglobin concentration; Lead-poisoned; Neurological symptoms; Child; Red cell distribution